Analysis of 31-year-old patient with SYNGAP1 gene defect points to importance of variants in broader splice regions and reveals developmental trajectory of SYNGAP1-associated phenotype: case report - Prchalova, Darina; Havlovicova, Marketa; Sterbova, Katalin; Stranecky, Viktor; Hancarova, Miroslava; Sedlacek, Zdenek (Bmc medical genetics, 2017)
BACKGROUND: Whole exome sequencing is a powerful tool for the analysis of genetically heterogeneous conditions. The prioritization of variants identified often focuses on nonsense, frameshift and canonical splice site mutations, and highly deleterious missense variants, although other defects can also play a role. The definition of the phenotype range and course of rare genetic conditions requires long-term clinical follow-up of patients. CASE PRESENTATION: We report an adult female patient with severe intellectual disability, severe speech delay, epilepsy, autistic features, aggressiveness, sleep problems, broad-based clumsy gait and constipation. Whole exome sequencing identified a de novo mutation in the SYNGAP1 gene. The variant was located in the broader splice donor region of intron 10 and replaced G by A at position +5 of the splice site. The variant was predicted in silico and shown experimentally to abolish the regular splice site and to activate a cryptic donor site within exon 10, causing frameshift and premature termination. The overall clinical picture of the patient corresponded well with the characteristic SYNGAP1-associated phenotype observed in previously reported patients. However, our patient was 31 years old which contrasted with most other published SYNGAP1 cases who were much younger. Our patient had a significant growth delay and microcephaly. Both features normalised later, although the head circumference stayed only slightly above the lower limit of the norm. The patient had a delayed puberty. Her cognitive and language performance remained at the level of a one-year-old child even in adulthood and showed a slow decline. Myopathic facial features and facial dysmorphism became more pronounced with age. Although the gait of the patient was unsteady in childhood, more severe gait problems developed in her teens. While the seizures remained well-controlled, her aggressive behaviour worsened with age and required extensive medication. CONCLUSIONS: The finding in our patient underscores the notion that the interpretation of variants identified using whole exome sequencing should focus not only on variants in the canonical splice dinucleotides GT and AG, but also on broader splice regions. The long-term clinical follow-up of our patient contributes to the knowledge of the developmental trajectory in individuals with SYNGAP1 gene defects.
Keywords: sekvence nukleotidů; fenotyp; Intellectual Disability; Microcephaly; mutace; mikročipová analýza; Phenotype; karyotypizace; genetická variace; mikrocefalie; následné studie; Sequence Analysis, DNA; sekvenční analýza DNA; Karyotyping; Adult; dospělí; proteiny aktivující GTPasu ras; Genomics; Follow-Up Studies; ras GTPase-Activating Proteins; exom; lidé; Exome; ženské pohlaví; Humans; Microarray Analysis; Base Sequence; Mutation; Genetic Variation; Female; mentální retardace; genomika